"Semeja esti prado egual de paraíso" : Gonzalo de Berceo : Milagros de nuestra señora - Vasas, László (Acta Hispanica, 2012)
The present article analyses some of the features that characterise Mariology. First of all, itfocuses on the history of this peculiar area of theology, as a literary and epistemological code.The text itself, designated to illustrate the formation of a new literary and philosophicaldiscourse, is the well known compilation Miracles of Our Lady by Gonzalo de Berceo, withspecial regard to the allegoric Introduction to the same work. Allegory was the most widespreadnarrative figure of social cultural texture in the Middle Ages. The Marian cult was anextraordinary literary revelation in the Europe of the 11-13th centuries. The chain ofmetaphors defining the Introduction to the Miracles implies a universal theological allegoryconcerning the role of the Virgin in the salvation of humanity. The interpretation of somelandscape elements means not only the polysemic allegory for the creation of a cultural home butalso signifies the conception of a new symbolical rational order and the combination of culturalregisters. What is meant is the embedding of Christian narrative and a serious attempt tocreate a specific national and culturalpattern.